Housing Decisions, Family Types and Gender. A look across LIS countries - Mariacristina Rossi; Eva Sierminska (Luxembourg Income Study (LIS), 2015)
In this paper we shall examine homeownership trends over the past 3 to 4 decades and discuss differences related to the homeownership gap for women and men, with a focus on most recent trends. We shall compare differences in the US to those in countries with different institutional structures and shall pay particular attention to differences across family types. Our estimation techniques will allow us to discuss the role of determinants from a gender perspective. We find that single women are better off than single men without children and a reverse trend exists in families with children. The general negative effect for women remains for younger cohorts in the face of risking homeownership. The latest crisis did not change the general long-running trend of the homeownership gap except for the US and France. The findings of this paper could provide an international perspective on differential homeownership rates among women and men, across countries and over time. Given that the value of one's own home (home equity) is the largest financial reserve in a household's wealth portfolio, it is important to have a better understanding of the differences resulting from gender and family types.
Keywords: D1; D3; R2; J1; 330; Housing; Wealth; Gender; homeownership; time trends